2010
DOI: 10.4049/jimmunol.0903742
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Signaling Inhibitory Pathway Induced by Green Tea Polyphenol Epigallocatechin-3-Gallate through 67-kDa Laminin Receptor

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(97 citation statements)
references
References 52 publications
(65 reference statements)
6
91
0
Order By: Relevance
“…Recently, 67LR has been identified as a cell surface EGCG receptor that mediates the anti-inflammatory activity of EGCG. In macrophages, 67LR was shown to be involved in the inhibitory effect of EGCG on the LPS-induced TLR4 signaling and peptidoglycan-induced TLR2 signaling pathway [13,14]. It was also shown to be involved in the inhibitory effect of EGCG on the TLR4 signaling pathway in dendritic cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 67LR has been identified as a cell surface EGCG receptor that mediates the anti-inflammatory activity of EGCG. In macrophages, 67LR was shown to be involved in the inhibitory effect of EGCG on the LPS-induced TLR4 signaling and peptidoglycan-induced TLR2 signaling pathway [13,14]. It was also shown to be involved in the inhibitory effect of EGCG on the TLR4 signaling pathway in dendritic cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study also showed that TLR4-activated NF-κB and MAPK signalling pathways were suppressed by the up-regulation of Tollip [26]. Moreover, down-regulation of Tollip leads to abrogation of the suppressive effect of EGCG on TLR4-triggered inflammatory responses [18]. These results indicated that Tollip plays a pivotal role in the negative regulation of TLR4 signalling.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have shown that EGCG has a potential anti-inflammatory effect [18, 19] and reduces MMP-9 expression through a cell surface receptor, 67-kDa laminin receptor (67LR) [20]. Recently, it has been confirmed that 67LR is involved in the suppressive effect of EGCG on TLR4 expression in macrophages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the repression of these mediators of TLR4 at the protein level. We previously reported on the inhibitory effect of EGCG on TLR4 signaling by the EGCG receptor in a 67LR-dependent manner (34). However, little is known on the upstream mechanism.…”
Section: Discussionmentioning
confidence: 99%